Vitamin D deficiency and risk of myasthenia gravis: An evidence-based case report - Wijayanthie, Nadiyah; Wulandari, Yohannessa; Rahmawati, Anni (World Nutrition Journal, 2024)
Background: An autoimmune condition known as myasthenia gravis (MG) targets the receptors for neurotransmitter acetylcholine at the neuromuscular junction, resulting in inhibition of muscle contraction. This results in muscle weakness resulting in a decrease in quality of life. Immunoregulation and muscle contractility are known to play a role in vitamin D. Literature on how vitamin D affects myasthenia gravis risk has not been widely carried out and the results are still controversial.Objective: To evaluate the association between vitamin D and MG risk.Methods: The search of the literature was conducted from PubMed, Cochrane Library, Embase, and EBSCOhost with the eligibility criteria determined by the authors. The literature search was using MeSH Term, text word, and title/abstract.Results: Two articles were selected and critically appraised. The first article shows an odds ratio of 3.96 (CI95 1.26 to 12.52), which means that myasthenia gravis has vitamin D levels almost 4 times lower than healthy population. A case-control study that followed described a comparison of mean levels of vitamin D (25(OH)D) in myasthenia gravis (mean, 18.8±8.4 ng/mL) compared to healthy controls (26.3±6.1). ng/mL) (p <0.05). Both studies revealed a strong interaction between MG and vitamin D inadequacy. Conclusion: Both studies above support the theory that vitamin D deficiency is associated with the risk of developing MG.